Efficacy and safety of two generic copies of nimesulide in patients with low back pain or knee osteoarthritis - S. Jankovic; M. Sefik-Bukilica; K.V. Ilic; N. Vujasinovic-Stupar (PAGEPress Publications, 2011)
Low back pain and knee osteoarthritis are the most common causes of rheumatic troubles among all the nonspecific joint diseases. In the United States, low back pain (LBP) accounts for almost $ 20 billion in lost productivity annually (1), and more than $ 80 billion is spent each year in the management of the disorder (2). Currently, there is no currative treatment for both low back pain and knee osteoarthritis. Nonsteroid antiinflammatory drugs (NSAIDs) are widely used for symptomatic relief (3) due to their analgetic and anti-inflamatory effect...